Cervical Intervertebral Disc Disease in a Bitch - Camargo Santos, Rávila; Sales Gomes, Filipe Augusto; Oliveira Silva, Letícia; Vieira Costa, Daniel; Martins Oliveira, Iago (Acta Scientiae Veterinariae, 2026)
Background: Intervertebral Disc Disease (IVDD) is one of the leading causes of neurological disorders in dogs and is characterized by spinal cord compression due to displacement or herniation of the intervertebral disc into the vertebral canal and intervertebral foramen. The neurological signs vary according to the location and severity of spinal cord compression, ranging from pain to tetraplegia with hypoventilation. Diagnosis is based on clinical evaluation, neurological examination, and imaging studies, with magnetic resonance imaging considered the gold standard. The aim of this study was to report a clinical case of cervical IVDD in a bitch. Case: A 6-year-old mixed-breed bitch, weighing 5.3 kg, was initially evaluated by a general practitioner with a complaint of difficulty walking, possibly associated with cervical pain, showing temporary improvement following corticosteroid therapy. After recurrence of clinical signs upon discontinuation of the medication, complementary diagnostic tests were requested. The complete blood count revealed hyperproteinemia and leukopenia, while biochemical parameters were within normal limits. Computed tomography demonstrated compressive myelopathy secondary to C2-C3 disc extrusion, with moderate spinal cord compression and degeneration of additional cervical and thoracic intervertebral discs. Based on the diagnosis of cervical IVDD, decompressive surgery using the ventral slot technique was indicated. The procedure consisted of a ventral cervical approach with fenestration of the C2-C3 intervertebral space, creating a rectangular window in the annulus fibrosus for removal of the extruded nucleus pulposus, followed by removal of disc material from the vertebral canal until visualization of the spinal cord. The patient was hospitalized for 24 h and received analgesic, anti-inflammatory, and antimicrobial support. At discharge, due to clinical stability, the dog was prescribed oral anti-inflammatory and antibiotic therapy for home care. At the 15-day follow-up, the patient showed a favorable recovery, with normal ambulation and no evidence of pain or postural deficits. Discussion: The age range and lesion location at C2-C3 observed in this case are consistent with patterns described in the literature for Hansen type I IVDD. Although the patient was not a chondrodystrophic breed, which is commonly associated with this condition, the clinical presentation, progression, and therapeutic response support the diagnosis. The absence of severe neurological deficits highlights that cervical pain may be the only clinical sign in cases of disc extrusion in this region. Although magnetic resonance imaging is considered the modality of choice for evaluating spinal cord lesions, computed tomography was sufficient to identify the extrusion and guide surgical decision-making. For spinal cord decompression at the C2-C3 level, surgical treatment using the ventral slot technique was selected, as this approach is indicated in cases of persistent pain or the presence of moderate to severe neurological deficits. Physical therapy is often recommended as an adjunct to enhance postoperative recovery following decompressive surgery. However, in the present case, physiotherapy was not deemed necessary due to the patient’s favorable clinical response and absence of significant neurological deficits, with adequate return to ambulation and resolution of pain achieved solely with surgical intervention. The favorable prognosis observed, even without physiotherapy, underscores the importance of accurate neurolocalization, which allows for appropriate diagnosis and timely intervention. Keywords: canine, cervical compression, intervertebral disc, myelopathy. Título: Doença do disco intervertebral cervical em uma cadela Descritores: canino, compressão cervical, disco intervertebral, mielopatia.